Performance of typical plan concrete buildings under progressive collapse. (June 2021) - Panahi, Saeed; Zahrai, Seyed Mehdi
Highlights: Studying the effect of plan type on progressive collapse of RC buildings. Choosing typical plans (square/rectangular) and using alternative path method. Using LS-DYNA for 3D modeling of concrete buildings. Direct modeling of all rebars inside the concrete section. More vulnerability of rectangular building to progressive collapse. Abstract: Many engineers are interested in the progressive collapse phenomenon, considering multi-user typical buildings, construction bias toward economization and thus, reduction of material consumption. The key factor in progressive collapse is the disproportion between the initial and final damage which sometimes can lead to the destruction of the whole building. So, the efforts are focused to prevent the expansion of initial damage through some strategies such as strengthening some load-bearing elements or choosing a proper plan. GSA and UFC regulations are two very reliable resources regarding the progressive collapse in which the alternative path method (APM) is one of the most common methods to evaluate building response to progressive collapse. In this study, the influence of typical concrete building plans (i.e. square and rectangular) on progressive collapse is investigated by 3D modeling of the buildings using LS-DYNA finite element software and removing a corner column using APM, considering GSA and UFC regulations. The results indicate that removing a corner column in the rectangular building has more intense effects including doubling the downward collapse rate, increasing the shear and axial loads in columns by 1.5 times, reciprocating motion of shear loads and higher energy absorption rate in comparison with those in the square building.